(untitled) (Scientia Agropecuaria, 2021)
Species of the genus Cinchona are recognized for their effectiveness in treating malaria. For Peru, this genus is of greater importance regarding forestry and civic aspects, because it represents the richness of the plant resource. Nevertheless, nowadays Cinchona populations are strongly threatened by various anthropogenic activities. Cutervo National Park (PNC) is the Peruvian’s first Protected Natural Area (ANP) and is considered as a conservation unit for the genus Cinchona. Objective: Determine the genetic diversity and phylogenetic relationships of the species of the genus Cinchona that inhabit the PNC. Methods: We tested 13 samples using the matK marker and a phylogenetic tree was generated using the maximum likelihood method and bootstrap measures of phylogenetic support. Results: 8 number of haplotypes (h) were recorded, with haplotype diversity (Hd) 0.859 and nucleotide diversity (π) 0.35%, also identifying: C. calisaya, C. pubescens and C. pitayensis for the PNC; the phylogenetic tree showed C. pitayensis as conserved specie, meanwhile C. pubsecens is present in many groups. Conclusions: The high genetic diversity of Cinchona and haplotype record of C. calisaya, species with a national conservation category of "Vulnerable", increases the importance for biodiversity conservation of the PNC.